Trends of incidence and survival of patients with chronic myelomonocytic leukemia between 1999 and 2014: A comparison between Swiss and American population-based cancer registries. (April 2019) - Benzarti, Sonia; Daskalakis, Michael; Feller, Anita; Bacher, Vera Ulrike; Schnegg-Kaufmann, Annatina; Rüfer, Axel; Holbro, Andreas; Schmidt, Adrian; Benz, Rudolf; Solenthaler, Max; Stussi, Georg; Arndt, Volker; et al.
Highlights: Epidemiologic characteristics are comparable to other population-based registries. Relative survival (RS) in CMML remains generally poor. Different time trends in RS cannot be explained by HMA treatment. Diagnostic accuracy within prognostically distinct age-groups may influence RS. Further collection of population-based data in CMML patients is warranted. Abstract: Background: Chronic myelomonocytic leukemia (CMML) is a rare hematopoietic malignancy. Treatment with hypomethylating agents (HMA) was introduced between 2004 and 2006 but its impact on population-based survival remains controversial. The aim of this study was to investigate epidemiological characteristics and survival before and after introduction of HMA treatment. Methods: We performed a population-based analysis of CMML cases reported to the Cantonal Cancer Registries in Switzerland (SWISS) and the Surveillance, Epidemiology, and End Results (SEER) Program from the United States for 1999–2006 (before HMA) and 2007–2014 (after HMA). Time trends were compared for these two time periods. Results: 423 and 4144 new CMML cases were reported to the SWISS and SEER registries, respectively. We observed an increasing proportion of older patients ≥75 years in the SWISS (50.3%–62.3%) compared to a decreasing one in the SEER population (59.1%–55.1%). Age standardized incidence-rates were similar and remained stable in both countries (0.32–0.38 per 100'000 py). Relative survival (RS) improved significantly in the SEER (3 years 27%–37%; 5 years 19%–23%; p < 0.001 for both) but remained stable in the SWISS population (3 years 48% to 40%; 5 years 34% to 26%; n.s. for both). Conclusions: With the exception of opposing age-trends, epidemiologic characteristics are similar in both countries and comparable to other population-based registries. RS remains poor and different time trends of population-based survival cannot be faithfully explained by HMA but most likely by changes in diagnostic accuracy within prognostically distinct age-groups.